2004
DOI: 10.1159/000080405
|View full text |Cite
|
Sign up to set email alerts
|

Quality Management in Blood Salvage: Implementation of Quality Assurance and Variables Affecting Product Quality

Abstract: Implementation of quality management in intraoperative blood salvage with controls of product and process quality supports early recognition and repair of dysfunction if respective actions are laid down in the quality management handbook. In order to avoid insufficient quality and to improve process quality, a broad understanding of the processes and of the variables affecting quality is needed, which is based on experimental tests. For this purpose the use of fresh whole blood as test blood and of protein as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 11 publications
0
19
0
1
Order By: Relevance
“…19 Processing partially filled bowls is a possible option to increase RBC recovery but not recommended because of decreased elimination rates. 23,24 Data of this study suggest that in children washout rates were only minimally reduced from 99.5% to 99.0% due to a lower Hct and a slower filling of the 55-mL bowl. Therefore, the use of partially filled bowls in infants can be considered undesired, but under certain circumstances even recommended.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…19 Processing partially filled bowls is a possible option to increase RBC recovery but not recommended because of decreased elimination rates. 23,24 Data of this study suggest that in children washout rates were only minimally reduced from 99.5% to 99.0% due to a lower Hct and a slower filling of the 55-mL bowl. Therefore, the use of partially filled bowls in infants can be considered undesired, but under certain circumstances even recommended.…”
Section: Discussionmentioning
confidence: 75%
“…If the TB volume did not match the bowl volume, wound blood was only partly processed by ELECTA and RBC recovery rates were falsely calculated low . Processing partially filled bowls is a possible option to increase RBC recovery but not recommended because of decreased elimination rates . Data of this study suggest that in children washout rates were only minimally reduced from 99.5% to 99.0% due to a lower Hct and a slower filling of the 55‐mL bowl.…”
Section: Discussionmentioning
confidence: 83%
“…Within ICS this can be caused by the surgical procedure as well as occurring at the collection (aspiration method, vacuum pressures for example) or processing stages. It has been suggested that haemolysis levels may increase during machine use (Hansen et al, 2004).…”
mentioning
confidence: 99%
“…In general, in the ‘total amount approach’, all input and all output, including several cycles and the final emptying, are considered. In the ‘per cycle approach’ that is more feasible for clinical quality controls, only the blood input and the product of one cycle (one bowl filling and automatic processing) are considered .…”
Section: Methodsmentioning
confidence: 99%